Developing English Teaching Instruction Based on Islamic Values in Non-Formal Education for The Children of Indonesia - Andi Hudriati; Rusdiah Rusdiah; Sulastri Sulastri (Pascasarjana Universitas Negeri Makassar, 2021)
One of the primary goals of studying English is to improve one's capacity to communicate in English. Islamic-based English classes for children at a local Mosque are ideal since they are provided with Islamic-based English materials derived from Islamic principles and tailored to the needs of Muslim youngsters while learning a second language. The present study aims to investigate an Islamic-based language learning instruction suitable for children in a non-formal setting. The study employs a qualitative research approach which observes and surveys Indonesian language and religious teachers to develop a suitable model for children in an informal setting. The results of the study revealed a means to enhance knowledge about Islam, while learning English as a tool of communication. The following conclusions can be taken from the stated results and discussions; (1) the planning and implementation of Islamic-based English language instruction in non-formal setting have not been optimally implemented thus far therefore the study provided an Islamic-based language instruction suitable for children, (2) educators require innovation in planning and implementing authentic learning for children since they are characterized by their playful nature and learn best by considering such nature, and (3) the foundations of Islam are best taught in early childhood, hence should be prioritized as the content material of their learning.